2020
DOI: 10.1111/jcpp.13285
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional links between adolescent brain function and substance use moderated by cognitive control

Abstract: Background: No clear consensus exists as to whether neurodevelopmental abnormalities among substance users reflect predisposing neural risk factors, neurotoxic effects of substances, or both. Using a longitudinal design, we examined developmental patterns of the bidirectional links between neural mechanisms and substance use throughout adolescence. Method: 167 adolescents (aged 13-14 years at Time 1, 53% male) were assessed annually four times. Risk-related neural processing was assessed by blood-oxygen-level-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, adolescents with higher levels of disinhibition are more likely than their peers to escalate use, use problematically, and eventually develop a substance use disorder (Iacono et al., 2008; Young et al., 2009). Continued exposure to environmental risk, including impaired parenting, suboptimal schooling, peer rejection, or an antisocial peer group, some of which elicited or selected by children themselves, as well as substance use itself, will exacerbate both disinhibition and externalizing psychopathology, and may have direct effects on the developing adolescent brain, leading to further deviations in control, reward, and emotionality processes (e.g., Kim‐Spoon et al, in press; Malone et al., 2014; Wilson et al, in press). And these processes will continue to play out into adulthood, with persistently high levels of disinhibition, increased likelihood of antisocial behavior and ongoing substance use, and associated psychosocial impairment.…”
Section: A Developmental Framework For Investigating Personality–psychopathology Linksmentioning
confidence: 99%
“…However, adolescents with higher levels of disinhibition are more likely than their peers to escalate use, use problematically, and eventually develop a substance use disorder (Iacono et al., 2008; Young et al., 2009). Continued exposure to environmental risk, including impaired parenting, suboptimal schooling, peer rejection, or an antisocial peer group, some of which elicited or selected by children themselves, as well as substance use itself, will exacerbate both disinhibition and externalizing psychopathology, and may have direct effects on the developing adolescent brain, leading to further deviations in control, reward, and emotionality processes (e.g., Kim‐Spoon et al, in press; Malone et al., 2014; Wilson et al, in press). And these processes will continue to play out into adulthood, with persistently high levels of disinhibition, increased likelihood of antisocial behavior and ongoing substance use, and associated psychosocial impairment.…”
Section: A Developmental Framework For Investigating Personality–psychopathology Linksmentioning
confidence: 99%
“…For example, EF predicts a host of behavioral and clinical outcomes including academic achievement (Miller et al, 2012), social skills (Miller & Hinshaw, 2010), and wellbeing (Cotrena et al, 2016. Deficits in adolescent EF have also been linked to substance use (Kim-Spoon et al, 2020), depression…”
Section: Introductionmentioning
confidence: 99%
“…For example, EF predicts a host of behavioral and clinical outcomes including academic achievement (Miller et al., 2012), social skills (Miller & Hinshaw, 2010), and wellbeing (Cotrena et al., 2016). Deficits in adolescent EF have also been linked to substance use (Kim‐Spoon et al., 2020), depression (Melendez‐Torres et al., 2016), as well as conduct disorders (Nigg & Huang‐Pollock, 2003), and are considered a key transdiagnostic risk factor for the development of psychopathology (Nolen‐Hoeksema & Watkins, 2011; Snyder et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that frontostriatal, frontolimbic and frontocerebellar systems are altered as a consequence of use [27]. Others have reported increasing risk-related insular cortex activation with prolonged substance use [28 ▪▪ ]. Using longitudinal cohorts to predict the emergence of substance use, investigators reported that both decreased anterior cingulate cortex volume [29] and blunted orbitofrontal cortex activation during reward outcome [30 ▪▪ ] predicted greater risk for substance and alcohol use initiation.…”
Section: Longitudinalmentioning
confidence: 99%